The reproductive parameters, lifestyle and health factors in relation to physiological menopausal symptoms in Slovak women - Luptáková, Lenka; Siváková, Daniela; Michnová, Alexandra; Čerňanová, Veronika; Cvíčelová, Marta; Danková, Zuzana (Anthropological Review, 2013)
Menopause is associated with various physiological symptoms which can be related to the most common health problems in menopausal women and a decrease in their quality of life. Determinants of experiencing menopausal symptoms are complex because they include reproductive, environmental, lifestyle and social factors. The aim of this study is to assess whether selected reproductive, lifestyle and health factors are associated with the occurence of hot flushes, night sweats, palpitations, dizzy spells and/or pins and needles in the hands and feet. A total of 346 women aged between 39 and 59 years living in Slovakia were recruited for this cross-sectional survey. Data on menopausal symptoms and potential confounders were collected by questionnaire. Logistic regression analysis revealed an independent effect of peri-/postmenopausal status and depressed mood on the manifestation of hot flushes. Analysis results for night sweats were significant for age, depressed mood and current smoking at p<0.05 while, of all input parameters, only age and depressed mood were significant predictors of palpitations. Logistic regression also revealed the effect of sport and depressed mood on dizzy spells. Depressed women, (B=0.677) and those who did not participate in sporting activities (B= –0.969) suffered more often from dizzy spells. Pins and needles in hands and feet were influenced by peri-/postmenopausal status (B=1.036), by higher numbers of pregnancy (B=0.260) and depressed mood (B=0.505). Potentially modifiable factors, such as current smoking, lack of sport, depressed mood and the number of pregnancies can predispose a woman to a higher prevalence of some of these physiological menopausal symptoms.